Potential Lines and Hybrids Developed from Modified Reciprocal Recurrent Selection in Maize - Sujin Jenweerawat; Chokechai Aekatasanawan; Paisan Laosuwan; Arnel R. Hallauer (Agriculture and Natural Resources, 2010)
A single-cross hybrid is the ultimate commercial product from maize breeding programs. Modified reciprocal recurrent selection (MRRS) is an alternative selection method for inbred and hybrid development. The objectives of this study were to assess lines and hybrids developed from MRRS in Suwan1(S)C11 and KS6(S)C3 maize populations with inbred testers Ki 47 and Ki 46, respectively. Twenty-five S4 lines, which corresponded to the 25 top-yielding testcrosses from 250 S1 testcrosses with inbred tester in each C0 population, were used to produce 50 testcross hybrids with their inbred tester. Ten S4 lines, which corresponded to the 10 top-yielding testcrosses, were also used in a factorial cross to make 100 interpopulation hybrids. The 150 hybrids and their 50 S5 lines were evaluated separately at two locations. The results indicated that the 10 top-yielding hybrids were five from Suwan1(S)C11-S4 × Ki 47, two from KS6(S)C3-S4 × Ki 46 and three from interpopulation hybrids with significantly higher (P < 0.05) grain yield than the hybrid check, Suwan 3851, by two, one and two hybrids, respectively. In addition, three hybrids from Suwan1(S)C11-S4 × Ki 47 had highly significant (P < 0.01) grain yield. The top 10 hybrids had similar values to the check for average days to 50% anthesis and silking, root and stalk lodging, foliar diseases and grain shelling, but had higher plant and ear heights. Parental lines of the top 10 hybrids were seven lines from Suwan1(S)C11 and four lines from KS6(S)C3. Their S5 lines, which had yields as high as the inbred check Ki 47, were five and three lines, respectively. In addition, the lines were not different from the check in other agronomic traits, except for days to flowering and plant height. In conclusion, the MRRS program was effective for the development of potential lines and hybrids for further commercial hybrid production.